2021
DOI: 10.1177/00494755211016652
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon variant of erythema nodosum leprosum responding well to methotrexate: Report of two cases

Abstract: Reactions in leprosy are acute inflammatory episodes that can be classified as type I or type II. Recognition and timely management of these patients is critical to avoid permanent disability. We present two cases of erythema nodosum leprosum, presenting with recurrent atypical features, responding well to a low dose of methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Several studies have reported alternative therapies for ENL, such as clofazimine, pentoxifylline, cyclosporine, azathioprine, etanercept, colchicine, chloroquine, minocycline, and zinc. However, the efficacies of these drugs were still varied [10,34].…”
Section: N Discussionmentioning
confidence: 99%
“…Several studies have reported alternative therapies for ENL, such as clofazimine, pentoxifylline, cyclosporine, azathioprine, etanercept, colchicine, chloroquine, minocycline, and zinc. However, the efficacies of these drugs were still varied [10,34].…”
Section: N Discussionmentioning
confidence: 99%
“…We read with interest the short report by Rani et al entitled "An uncommon variant of erythema nodosum leprosum responding well to methotrexate: Report of two cases." 1 The authors describe two cases of erythema nodosum leprosum (ENL) with 'atypical features' and good response to low dose methotrexate. A closer examination of the report reveals several treatment concerns that hamper the prospect of drawing meaningful conclusions from this report.…”
Section: Sirmentioning
confidence: 99%